Thermal and electrical behaviors of acid functionalized MWCNT/ABC-type triblock copolymer grafted-MWCNT nanocomposites - Yilmaz, Serpil; Coskun, Mehmet (Taylor & Francis Inc, 2017)
In this work, ABC-type triblock copolymer grafted onto the surface of the MWCNT/acid functionalized MWCNT (MWCNT-COOH) composites were prepared and the properties of nanocomposites were characterized extensively using differential scanning calorimetry (DSC), scanning electronic microscopy (SEM), thermogravimetric analysis (TGA), ac electrical conductivity and dielectrical measurements.DSC study showed that the glass transition temperatures of the nanocomposites are a some higher than that of the matrix polymer. The increase in oxidized MWCNT in the nanocomposite improved the thermal stability of the composite, according to initial decomposition temperatures. The ac electrical conductivity has increased moderately with increasing frequency, but has increased slowly with increase in the oxidized MWCNT content in the nanocomposites. The electrical conductivity increases slowly with increasing temperature to about the glass transition temperature, then it increases faster. The dielectric constants for the matrix polymer and all the composites decreases slightly with increasing frequency from 0.1kHz to 2.0kHz. The dielectric constant increases slightly with increasing temperature up to about the glass transition temperature region and then the increase in temperature is accelerated the increase in the dielectric constant.
Keywords: oxidized MWCNT; polymer grafted MWCNT; composite; thermal; electrical